Kajian Edukatif Tentang Pengaruh Staycation dan Akomodasi Syariah Terhadap Kondisi Mental Mahasiswa di Lingkungan Perguruan Tinggi - Dias Widiawati; Moh Farih Fahmi; A’rasy Fahrullah; Sri Abidah Suryaningsih (Journal of Education and Learning Sciences, 2026)
This study aims to analyze the influence of staycation decisions and the choice of sharia-compliant accommodation on students' mental health. Students often experience academic stress that can impact their psychological well-being, therefore alternative recovery activities are needed. This study used a quantitative approach with an associative method. Data were collected through questionnaires distributed to 150 students selected using a purposive sampling technique. Data analysis used multiple linear regression with SPSS. The results showed that staycation decisions had a positive and significant influence on students' mental health. The choice of sharia-compliant accommodation also had a positive and significant influence on students' mental health. Simultaneously, both variables significantly influenced students' mental health. Staycation activities supported by comfortable and sharia-compliant accommodation can be an effective strategy to reduce stress and improve student well-being.